MIDDLE PRECLASSIC POTTERY PRODUCTION AND EXCHANGE IN THE NORTHERN MAYA LOWLANDS: AN ICP-MS ANALYSIS. Issue 3 (2022) - Parker, Evan; Bey, George J.; Gu, Jiyan; Ward, Timothy; Gallareta Negrón, Tomás
Abstract: Evidence of complex and widespread occupations during the Middle Preclassic (1000–350 b.c. ) have been identified throughout the Northern Maya Lowlands and are associated with both Mamom and pre-Mamom ceramics. Beyond typological information based on the visual examination of paste, slip, and surface treatment, archaeologists know little about the technology or economics of pottery production and exchange of this period. In this study, we analyze Middle Preclassic ceramics from four sites in northwest Yucatan, using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to determine the chemical variation that exists between and within different ceramic production areas. The analysis indicates that production occurred locally by the late Middle Preclassic (700–350 b.c. ), and that the earliest pottery produced in the Northern Maya Lowlands, at the sites of Komchen and Kiuic, was compositionally linked to later phases of production. This means that the first ceramic complexes of the Northern Lowlands were locally produced and not the result of migrants bringing pottery from elsewhere. The study reveals it is possible to identify the origin of Middle Preclassic ceramics by their chemical signature and that compositional variation existed at the site level over time.